DnBP-induced thyroid disrupting activities in GH3 cells via integrin αvβ3 and ERK1/2 activation. (December 2018) - Kong, Dongdong; Liu, Yun; Zuo, Rui; Li, Jian
Abstract: Di-n-butylphthalate (DnBP) exhibits alarming thyroid disrupting activities. However, the toxic mechanism of DnBP is not completely understood. In this study, we investigated the mechanism of DnBP in thyroid disruption. Rat pituitary tumor cell lines (GH3) were treated with DnBP in different scenarios, and cell viabilities, target gene transcriptions and protein levels were measured accordingly. The results showed that after treatment with DnBP (20 μmol/L), cell proliferation increased to 114.69% ( p  < 0.01) and c-fos gene was up-regulated by 1.57-fold ( p  < 0.01). Both nuclear thyroid hormone receptor β (TR β ) and membrane TR ( integrin α v and integrin β 3 ) genes were up-regulated by 1.31-, 1.08- and 2.39-fold ( p  < 0.01), respectively, the latter was inhibited by Arg-Gly-Asp (RGD) peptides; the macromolecular DnBP-BSA was unable to bind nuclear TRs, but still promoted cell proliferation to 104.18% and up-regulated c-fos by 2.99-fold ( p  < 0.01); after silencing TRβ gene, cell proliferation (106.64%, p  < 0.05) and up-regulation of c-fos (1.23-fold, p  < 0.01) were also observed. All of these findings indicated the existence of non-genomic pathway for DnBP-induced thyroid disruption. Finally, DnBP activated the downstream extracellular regulated protein kinases (ERK1/2) pathway, up-regulating Mapk1 (1.15-, p  < 0.05), Mapk3 (1.26-fold, p  < 0.01) and increasing protein levels of p -ERK ( p  < 0.01); notably, DnBP-induced ERK1/2 activation along with c-fos up-regulation were attenuated by PD98059 (ERK1/2 inhibitor). Taken together, it could be suggested that integrin αv β3 and ERK1/2 pathway play significant roles in DnBP-induced thyroid disruption, and this novel mechanism warrants further investigation in living organisms. Graphical abstract: Highlights: DnBP induced cell proliferation to GH3 cells. DnBP induced thyroid disruption to GH3 cells through non-genomic pathways. DnBP induced thyroid disruption to GH3 cells via integrin αv β3 and ERK1/2 pathway.